The Distributive Impact of Taxes and Expenditures in Colombia - Jairo, Nunez; Olivieri, Sergio; Parra, Julieth; Pico, Julieth (World Bank, Washington, DC, 2020)
Colombia has reduced extreme poverty in the past 16 years by almost half, moderate poverty by 22 percentage points, and made more than four million Colombians jump the threshold of multidimensional poverty. However, it remains one of the most unequal countries in the region, after Brazil and Panama. Fiscal policy is one of the instruments that allow governments to speed up the decline in inequality levels and reduce poverty. This study presents an exhaustive and comprehensive analysis of the distributional impacts of taxes and expenditures in Colombia in 2017. It makes a methodological comparison with the Commitment to Equity, which was previously implemented, and includes multiple improvements in the methodology. The results suggest that the combined effect of taxes and social spending in Colombia contributes to poverty reduction between 0.3 and 2.6 percentage points for US$5.5 and US$3.2 per day per person respectively, while inequality is reduced by almost one Gini point. Taxes and direct transfers, as well as indirect transfers, are progressive and pro-poor, while indirect taxes are regressive and contribute to an increase in inequality. Finally, transfers in-kind for education and health services are progressive and contribute to the reduction of inequality.